Ik Shim, Royal Award recipient perseverance becomes beacon of success - Nur Hartini, Mohd Hatta (UMPSA, 2025)
GAMBANG, 8 November 2025 – Behind the success of becoming a System Engineer (Cybersecurity) at Perusahaan Otomobil Kedua Sdn. Bhd. (PERODUA), lies the story of the perseverance of a child who made the love and sacrifice of her mother the main source of strength.